Mathematical models for simulating Covid-19 contagion in Italy: first wave - Carf`ı, David; Donato, Alessia (Journal of Mathematical Economics and Finance; Vol 6 No 1 (2020): JMEF, Volume VI, Issue 1(10), Summer 2020DO - 10.14505/jmef.v6.1(10).03, 2020)
In this paper, we provide two approximating functions for some dynamics associated with the first wave of Covid-19 contagion in Italy. We consider also two particular cases of Sicily and Lombardy. We consider only the evolution of total infected cases and new daily cases. We show that the total infected cases need, in the time period considered, two different approximations. We approximate the daily infected curves by the first derivative of the above two functions. In the case of Lombardy, we consider a wider time interval to obtain an ultimate approximation.